Alone Together : Poetics of the Passions in Late Medieval Iberia - Berlin, Henry (Book collections on Project MUSE., 2021)
"The turn of the fifteenth century saw an explosion of literature throughout Iberia that was not just sentimental, but about sentiment. Alone Together reveals the political, ethical, and poetic dimensions of this phenomenon, which was among the most important of the substantial changes in intellectual and literary culture taking place in the crowns of Portugal, Castile, and Aragon. With careful analyses of lyric poetry, sentimental prose, and wide-ranging treatises in multiple languages, this study foregrounds the dense web of relations among these genres and linguistic and cultural traditions. Drawing on Stoic and early monastic thought, authors such as the Marques de Santillana, Ausiàs March, and Alfonso de Madrigal explored the unifying potential of shared emotion in an ethical rehabilitation that cut across the personal and political, exalting friendly conversation, civic communication, and collective poetic composition. In his readings of these authors, Henry Berlin references recent work on lyric theory and the history and theory of emotion, from classical antiquity to the modern day. An exploration of the political and poetic potential of shared emotion, Alone Together shows how a heuristic focus on the notion of passion is illuminating for broader ongoing discussions about the nature of emotion, the lyric, and subjectivity."--